The association between serum klotho protein and stroke: a cross-sectional study from NHANES 2007–2016 - Xu, Hongjia; Ding, Yiming; Zhang, Ye; Li, Jianwen; Zhou, Shiyue; Wang, Dewei; Xing, Xinyue; Ma, Xiaoyu; Wang, Cunfu; Xu, Shunliang (Frontiers in Neurology, 2025)
ObjectiveSerum klotho protein is a protein with anti-aging effects. Since the relationship between serum klotho and Stroke remains rather ambiguous, this research probed into the potential correlation between serum klotho concentration and Stroke.MethodsThis study employed a cross-sectional design and incorporated population data from the NHANES from 2007 to 2016. Weighted univariate and multivariate logistic regression models were utilized to inspect the relationship between klotho and Stroke. Stratified analyses and interaction tests were carried out to explore the latent correlation between klotho and Stroke. Finally, a fitted smooth curve was adopted to depict the non-linear relationship.ResultsIn this study, after excluding all the missing data, a total of 12,414 participants were encompassed, including 450 Stroke individuals. After adjusting for all covariates, higher klotho was associated with a lower prevalence of Stroke. According to the subgroup analyses and interaction tests, age, gender, race, BMI, hypertension, diabetes mellitus, family members, drinker and smoker were not significantly correlated with the influence of klotho and Stroke. After adjusting for all covariates, higher klotho was associated with a lower prevalence of stroke [OR: 0.68, 95% CI: 0.47–0.99].ConclusionThis study disclosed the negative correlation between serum klotho protein levels and the prevalence of Stroke. Further prospective studies are requisite to investigate the impact of serum klotho protein levels on Stroke and determine the causal relationship.